Crown lengthening and direct composite onlay restoration with polyethylene fiber ribbon used as core materials of endodontically treated teeth: A case report - Nunik R. Apriliyani; Rebecca A. Kuncoro; Ema Mulyawati; Yulita Kristanti (Journal of Dentomaxillofacial Science, 2021)
Objective: To manage endodontically treated teeth with subgingival margin and gingival polyp. Methods: A 22-year-old female came to the Conservative Dentistry Clinic at the University of Gadjah Mada Dental Hospital with the chief complaint of upper left molars felt uncomfortable due to the food impaction and the adjacent gingiva of the cavity was enlarged. Objective examination, showed 26 had a cavity on mesio-occlusal surface of dentin depth accompanied by gingival polyps in the mesial region. Radiographic examination, showed radiolucent area on the mesio-occlusal surface with depth reaching the dental pulp. Based on those examinations, 26 necrosis of pulp with gingival polyp diagnosis was made. The treatment planning of the patient were root canal treatment, crown lengthening, direct composite onlay restoration with polyethylene fiber ribbon used as core materials, and dental health education. Results: After a two-year recall, the clinical appearance of the fiber-reinforced composite, showed no sign of marginal discoloration or alterations of the proximal and occlusal anatomy and the radiograph showed no marginal gap. Conclusion: Crown lengthening procedure was done to prevent biologic width violation and to ensure a good marginal seal with the final restoration. Application of polyethylene fiber ribbons can be used to reinforce tooth structure. Direct composite onlay restoration was chosen by reason of amount of healthy tooth structure remaining and preserving a sound tooth structure.